COMMUNITY EMPOWERMENT THROUGH PRODUCT INNOVATION: COCOPEAT AS A SUPERIOR GROWING MEDIUM FOR URBAN FARMING TO IMPROVE THE ECONOMY OF MAMUJU REGENCY - Ahmad, Srifatmawati; Sudarman; Ridwan (LPPM Univ. Ibn Khaldun Bogor, 2025)
This Community Service program partners with the community in Sumare Village, Simboro District, Mamuju Regency, which is one of the villages inhabited by farmer groups. Based on initial observations, the farmer groups still rely on traditional methods without adopting modern agricultural technologies such as plastic mulch, drip irrigation, greenhouses, or planting media such as Cocopeat. Production is often a burden, especially when fertilizer prices rise and superior seeds are scarce on the market. Many farmer groups rely on middlemen to obtain fertilizer/seeds, with a burdensome post-harvest payment scheme. One product resulting from the use of coconut fiber is cocopeat. Cocopeat is a processed product of coconut fiber waste, where the separation of coconut fiber produces coconut powder that can be used as a planting medium. The main target is to create new household-scale business units and urban farming communities based on cocopeat, so as to be able to encourage additional income, open informal jobs, and strengthen community food security. The Cahaya Tani Farmer Group has utilized coconut fiber waste to reduce environmental pollution while being an alternative good planting medium for plants.